2009
DOI: 10.1097/bor.0b013e32831de4e7
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic disease in vasculitis

Abstract: Purpose of review To give an overview of recent clinical findings of thromboembolic disease in vasculitis and provide insight into possible explanations of the association between thrombosis and inflammation. Recent findings A high incidence of venous thrombotic events has recently been described in four distinct cohorts of patients with antineutrophil cytoplasmic antibodies-associated vasculitis (AAV), especially during periods of active disease. No factors other than the vasculitis itself have been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 56 publications
4
61
1
2
Order By: Relevance
“…Studies in four distinct AAV patient cohorts have identified an increased incidence of venous thromboembolic events (VTE), which does not seem to be attributable to conventional prothrombotic risk factors. 16,17 Meanwhile, anti-plasminogen antibodies correlated with VTE episodes in PR3-ANCA patients. 3 Although one of the Dutch patients with particularly high titers of anti-plasminogen antibodies had a history of deep venous thrombosis, we do not have comprehensive data on VTE episodes in the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in four distinct AAV patient cohorts have identified an increased incidence of venous thromboembolic events (VTE), which does not seem to be attributable to conventional prothrombotic risk factors. 16,17 Meanwhile, anti-plasminogen antibodies correlated with VTE episodes in PR3-ANCA patients. 3 Although one of the Dutch patients with particularly high titers of anti-plasminogen antibodies had a history of deep venous thrombosis, we do not have comprehensive data on VTE episodes in the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have suggested a link between inflammation and thrombosis and were recently reviewed (43). For example, active vasculitis in ANCAassociated vasculitides as well as Behçet's disease is associated with deep venous thrombosis (43). It is believed that disruption of the endothelial layer due to the vasculitic process exposes active tissue factor, which in turn leads to activation of coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a link between active vascular inflammation and thrombosis in lupus is self-intuitive, and we believe that our patient's lupus flare was probably the trigger for his LAC-mediated thrombosis. In fact, several studies have suggested a link between inflammation and thrombosis and were recently reviewed (43). For example, active vasculitis in ANCAassociated vasculitides as well as Behçet's disease is associated with deep venous thrombosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial activation and injury are central to the pathogenesis of vasculitides with increased endothelial cell adhesion molecule expression, and a switch to a prothrombotic endothelial phenotype, both contributing to the vascular pathology (Tomasson et al, 2009;Blake et al, 1985). In systemic vasculitis impaired endothelial repair capacity of EPC was addressed and the significant inflammatory milieu could adversely affect EPC function, resulting in defective colony formation, adhesion and ability to integrate into vascular networks.…”
Section: Epcs In Vasculitismentioning
confidence: 99%